If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 3 = 86 Reorder the terms: 3 + 4n = 86 Solving 3 + 4n = 86 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4n = 86 + -3 Combine like terms: 3 + -3 = 0 0 + 4n = 86 + -3 4n = 86 + -3 Combine like terms: 86 + -3 = 83 4n = 83 Divide each side by '4'. n = 20.75 Simplifying n = 20.75
| -p+5(3p-2)+4= | | (5)(-2)+(5)(-2)(-3)= | | 20+-8x+30+-16x=180 | | -7r+6t-8s-r+12s+4t-t+2s-r= | | 6×12/2 | | -7x+4x+7+4x=(0-14)-(-8+5) | | 5-4(1-x)=21 | | 8x^2y^3z-2xyz+4x^3yz^2= | | -34(14x)+27(21x)=(75-75)+(-823+95) | | 2-x=-2(3x+4) | | 2X/3=3 | | 6x=(8-.25x)-(6-0.75x) | | (-4,3)M,=1/2 | | X/7=9=15 | | 2w=10+7w | | 3x^2-8xy+4y^2=6 | | 4x^2+378x-13631=0 | | 5+4h=9h | | 3(Mt+2)=7(4t+6) | | 50/6.25 | | 3x=(8-0.25x)-(3-.75x) | | 5/3*60 | | 2z+10=z | | 3(x+2)-4=2(4) | | ln(-1/2) | | -x+13=2x+1 | | 2c+3=50c-6 | | 6-5c=-4c | | -2a+3=9 | | 3(0)-9(3)=15 | | 2n-5=4n-7 | | 48=4n-4 |